Coordinated responses to individual tumor antigens by IgG antibody and CD8+ T cells following cancer vaccination. Issue 1 (5th April 2018) - Hulett, Tyler W.; Jensen, Shawn M.; Wilmarth, Phillip A.; Reddy, Ashok P.; Ballesteros-Merino, Carmen; Afentoulis, Michael E.; Dubay, Christopher; David, Larry L.; Fox, Bernard A.
Abstract : Background: One of today's greatest hurdles for cancer immunotherapy is the absence of information regarding which tumor antigens are already recognized by patients receiving immunotherapies, and whether those therapies then boost or generate an immune response against tumor proteins. For CD8+ T cells in particular, patient-specific immune recognition and responses at the level of individual tumor antigens are rarely characterized. Because of this, some immunologists have turned to serum antibodies as an alternative measure of antigen-specific anti-tumor immunity. In this work, we sought to simultaneously interrogate serum IgG and CD8+ T cell recognition of individual tumor antigens to determine whether antigen-specific serum IgG antibodies provide a window into the behavior of antigen-specific CD8+ T cell responses. Using antibody-based assays to evaluate immune response repertoires and focus T cell antigen exploration could afford substantial advantages for discovering and monitoring the anti-cancer immune responses of patients enrolled on clinical trials. Methods: We vaccinated female BALB/c mice with a novel combination of an autophagosome-enriched vaccine derived from 4T1 mammary carcinoma along with poly-I:C adjuvant, then screened serum for IgG binding to arrays of 15mer peptides containing known mutation sites in 4T1. Simultaneously, we primed CD8+ T cell cultures from these same animals with 8-11mer peptides derived from these antigens. These primed T cells were then stimulated to measure recognition of the peptides or live 4T1 cells by IFNγ release. Results: Vaccinated animals demonstrate increases in antigen-specific CD8+ T cell recognition of 4T1 tumor cells and peptides. For proteins confirmed in 4T1 cells and vaccine by mass spectrometry, there is a correlation between this increased CD8+ T cell IFNγ release and serum IgG binding to individual peptide antigens. Conclusions: These results suggest it is possible to observe some features of a patient's antigen-specific T cell repertoire via an antibody surrogate, which has implications for tumor antigen discovery and clinical monitoring of antigen-specific anti-tumor immunity.